A Study on Acid Rain and its Impacts (International Journal of Food and Nutritional Sciences, 2022)
In order to succeed in today, the harmful impacts of acid rain are recognized as one of the most major environmental concerns. Corrosive rain's impacts have been felt all over the world, mostly in developed nations that have a worldwide impact. In a large number of nations throughout the world, it has become a significant local ecological problem. The ecological effects of acid rain are the most obvious in aquatic environments such as streams, lakes, or marshes, where that would kill fish or other organisms. As acidic rainfall flows and through soil or into local waterways, it may remove aluminum through soil clay particles. When more acid is introduced to the environment, aluminum is released in higher amounts. The author of this article discusses acid rain and its effects on the ecosystem. The primary goal of this study is to get a better understanding of acid rain and its impacts. According to a recent research, acid rain's detrimental effects start far sooner than previously believed, putting forest productivity at risk by quietly degrading their food reserves in the soil.